Cortical surface variation in individuals with excessive smartphone use - Hirjak, Dusan; Henemann, Gudrun Maria; Schmitgen, Mike; Götz, Larissa; Wolf, Nadine D.; Kubera, Katharina Maria; Sambataro, Fabio; Leménager, Tagrid; Koenig, Julian; Wolf, Robert Christian (Developmental neurobiology, 2022)
Excessive smartphone use has been repeatedly related to adverse effects on mental health and psychological well-being in young adults. The continued investigation of the neurobiological mechanism underlying excessive smartphone use—sometimes also referred to as “smartphone addiction”(SPA)—is considered a top priority in system neuroscience research. Despite progress in the past years, cortical morphology associated with SPA is still poorly understood. Here, we used structural magnetic resonance imaging (MRI) at 3 T to investigate two cortical surface markers of distinct neurodevelopmental origin such as the complexity of cortical folding (CCF) and cortical thickness (CTh) in individuals with excessive smartphone use (n = 19) compared to individuals not fulfilling SPA criteria (n-SPA; n = 22). SPA was assessed using the Smartphone Addiction Inventory (SPAI). CCF and CTh were investigated using the Computational Anatomy Toolbox (CAT12). SPA individuals showed lower CCF in the right superior frontal gyrus as well as in the right caudal (cACC) and rostral anterior cingulate cortex (rACC) compared to n-SPA individuals (TFCE, uncorrected at p < 0.001). Following a dimensional approach, across the entire sample, CCF of the right cACC was significantly associated with SPAI total score, as well as with distinct SPAI subdimensions, particularly time spent with the device, compulsivity, and sleep interference in all participants (n = 41; p < 0.05, FDR-corrected). Collectively, these findings suggest that SPA is associated with aberrant structural maturation of regions important for cognitive control and emotional regulation.